The impact of public transport expansions on informality: the case of the S\~ao Paulo Metropolitan Region - Ana Isabel Moreno-Monroy; Frederico Ramos (European Regional Science Association (ERSA), 2015)
The S\~ao Paulo Metropolitan Region (SPMR) displays a strong core-periphery divide. Central areas concentrate the bulk of formal jobs while peripheral areas display high incidence of informal employment. This pattern is reinforced by a large deficit in urban transport provision. Against this background, we estimate the impact of expansions of the public transport system on local informality rates for the SPMR between 2000 and 2010. We compare the average changes in informality in areas which received new public transport infrastructure with the average changes in areas which were supposed to receive infrastructure according to official plans, but did not because of delays. After controlling for endogenous selection, we find that informality decreased on average 15 percent faster in areas receiving new public transport infrastructure compared to areas that faced project delays.
Keywords: F12; O14; O17; R12; 330; Urban transport; informality; Brazil; impact evaluation